Variability in Clones of Eucalyptus camaldulensis in Response to Elevated Carbon Dioxide and Temperature - Jayaraj, R. S. C.; Lalitha, S.; Balu, A.; Warrier, Rekha R. (Indian Forester, 2017)
Thirty clones of Eucalyptus identified as productive clones, through a systematic tree improvement programme at the Institute of Forest Genetics and Tree Breeding, Coimbatore were screened for their response to elevated carbon dioxide and temperature in Open Top Chambers (OTC). Based on Relative Growth Rate (RGR) and total biomass, clones were shortlisted. Seventeen clones which exhibited variation to the changes in elevated CO2 and elevated temperature were categorized as "climate change ready" clones those can withstand the adverse effects of climate change.